Chronic Wound Caring Experience with Telehealth - Ni Ketut Kardiyudiani; Josephine Daquioag Lorica (GLOBAL HEALTH SCIENCE GROUP, 2021)
Chronic wounds are often associated with slow healing time, patients with chronic wounds will have an impact on physiological, psychological, social and financial burdens. The pandemic situation encourages the use of telehealth for wound care, so it is important to analyze it. To explore the experiences of patients with chronic wounds and receiving telehealth care. Materials and Methods: This research method is a meta-analysis with a qualitative approach. An article search was conducted on Google Scholar and Science Direct, entering the keywords